Multifunctional Tunable Band-Limited Optical Coupled-Ring Reflector (CRR) Device Using Criss-Crossing Directional Coupler - Dingel, Benjamin (Archīum Ateneo, 2020)
We present a new; multifunctional; tunable coupled-ring reflector (CRR) device where the two cascaded microring resonator-based All-Pass Filters (APFs) are now interconnected using a “crisscrossed port connection arrangement and then directly coupled” by a third directional coupler. We derive analytically and investigate numerically its intensity response. We show that it has many unique features such as: (i) asymmetric stopband/passband property; (ii) tunable dual-narrowband passband filter; and (iii) a unique quasi-interleaver characterized by dual-narrowband passband filter interleaved with broadband stopband filter. We also establish the critical parameter relationships that describe these rich responses and compare them to the typical CRR.